PERCEIVED MEDIA INFLUENCE AND POLITICAL PARTICIPATION: A MIXED-METHODS STUDY OF NIGERIAN STUDENTS - Sanusi, Bernice Oluwalanu; Kuye-Aremu, Oluwakemi Khadijat; Lukman, Abdulkareem; Adeyemo, Oluwafikunayomi Demilade (African Journal of Social and Behavioural Sciences, 2025)
This study examines how perceptions of media influence affect political attitudes and participation, emphasising corrective political actions among 392 students from Summit University and Federal Polytechnic, Offa. A cross-sectional survey and regression analysis approach was used, with offline participation (e.g., protests, rallies, petitions) and online participation (e.g., posting political content, influencing voter behaviour) as outcome variables. Demographic and psychological factors, such as age, gender, education, political interest, efficacy, and ideological extremity, were included as controls in regression analyses. Key findings reveal that a more significant third-person perception gap significantly increases both offline (B = 0.35, p < .01) and online (B = 0.29, p < .05) political participation. Hostile media perceptions also predict higher offline (B = 0.41, p < .01) and online (B = 0.33, p < .05) engagement. Interaction effects between third-person perception and media hostility further amplify political activism. Political interest and knowledge were positively linked to both participation types, while internet use was specifically associated with online activism. This study examines how perceptions of media bias and influence drive political participation among Nigerian students, with implications for media literacy in polarized democracies.